Associations between nollywood movies and risky sexual behaviours among in-school youths in Nigeria: an ongoing study (2020)
Nollywood, the second largest movie industry in the world after America’s Hollywood, is Nigeria’s movie industry. This ongoing study investigates how sexual messages and scenes are communicated to viewers and if there is correlation between the pattern of Nollywood movies exposure and sexual behaviour of in-school adolescents in the southwestern part of Nigeria. Data will be collected from the participants through questionnaire while content of popular Nollywood movies among the participants will be content analyzed. It is expected that this study will provide information about the frequency of sexual scenes and how risky sexual behaviours are portrayed in Nollywood movies. Secondly, it is expected that this study will show the types of relationships that exist between movie exposure behaviour and sexual behaviour in the study population.